2008
DOI: 10.1063/1.3010867
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of Tb3+ doped TeO2–ZnO–Na2O–PbO glasses containing silver nanoparticles

Abstract: Luminescence properties of Tb 3+ doped TeO 2 -ZnO-Na 2 O -PbO glasses containing silver nanoparticles ͑NPs͒ were investigated. The absorption band due to the surface plasmon resonance in the NPs was observed. Its amplitude increases with the heat treatment of the samples that controls the nucleation of the NPs. Tb 3+ emission bands centered at Ϸ485, Ϸ550, Ϸ585, and Ϸ623 nm were detected for excitation at 377 nm. The whole spectrum is intensified by the appropriate annealing time of the samples. Enhancement by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…Moreover, previous studies with tellurium oxide glasses indicated that the symmetry around the RE ions does not change with the heat treatment. 17,18 Therefore the results indicate that the simultaneous presence of Tb 3+ and Eu 3+ ions is essential to observe the strong luminescence in the orange-red region.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, previous studies with tellurium oxide glasses indicated that the symmetry around the RE ions does not change with the heat treatment. 17,18 Therefore the results indicate that the simultaneous presence of Tb 3+ and Eu 3+ ions is essential to observe the strong luminescence in the orange-red region.…”
Section: Resultsmentioning
confidence: 95%
“…[1][2][3]7,8,13 Recently nucleation of metallic nanoparticles ͑NPs͒ inside tellurium oxide glasses was reported. [14][15][16][17][18] In all cases studied the presence of NPs contributes to enhance the material's luminescence efficiency either due to ET from the NPs to the RE ions or by influence of the large local field on the RE ions positioned in the vicinity of the NPs. Indeed the presence of silver nanostructures in TeO 2 -PbO-GeO 2 In this work we present the first luminescence study of Tb 3+ / Eu 3+ doped TeO 2 -ZnO-Na 2 O -PbO glass containing silver NPs.…”
Section: -13mentioning
confidence: 99%
“…The peaks at 488, 545, 585, and 620 nm can be assigned to the intra-4f 5 D 4 ! 7 F j transitions ( j ¼ 6, 5, 4, 3) of Tb 3þ ions, [17][18][19][20] respectively. The strongest peak at 545 nm, splitting into two lines (543 nm and 547 nm), is assigned to the 5 D 4 !…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Terbium (Tb) has frequently been used as dopant, because of its strong radiative intra-4f transitions in the green light region, which is very important to optoelectronic devices such as light-emitting diodes. [12][13][14][15][16][17][18][19][20] The photoluminescence (PL) properties of Tb-doped SiC(SiC:Tb) materials have been researched by several groups. [12][13][14][15] Sendova-Vassileva et al 12,13 reported the room-temperature (RT) PL of Tb 3þ ions doped in amorphous SiC:H (a-SiC:H) thin films prepared by magnetron cosputtering.…”
Section: Introductionmentioning
confidence: 99%
“…Among RE 3+ ions, dysprosium ion (Dy 3+ ) in oxide glasses has narrow intense emissions at blue ( 4 F 9/2 → 6 H 13/2 ) and yellow ( 4 F 9/2 → 6 H 15/2 ) regions, and exhibits warm yellowish-white light to * E-mail: lhai8686@yahoo.com naked eyes [39][40][41][42][43][44]. However, the effective excitation region of Dy 3+ is restricted to the long-wave ultraviolet (UVA) area, showing the insufficiency in medium-wave ultraviolet (UVB) and short-wave ultraviolet (UVC) regions [45,46].…”
Section: Introductionmentioning
confidence: 99%